Flowers in the attic [videorecording (DVD)] - Burstyn, Ellen, 1932-; Graham, Heather, 1970-; Shipka, Kiernan, 1999-; Bruce, Dylan, 1980-; Andrews, V. C. (Virginia C.) (A&E Television Networks, 2014)
A gothic story of four siblings who, after the death of their father, are torn from a peaceful life and subjected to abuse resulting from a dark, family secret. Abandoned by their mother and forced to endure unimaginable treatment living in the attic of their grandparents' mansion, the children form their own family unit. But as the oldest boy and girl come of age, they are entrapped by their family's sordid past as they try to survive and escape the harsh living conditions.